STEEL ROOF STRUCTURE STRENGTH ANALYSIS USING 2D FINITE ELEMENT METHOD - Iman, Miftahul; Nelfia, Lisa Okri; Manurung, Edison Hatoguan (Universitas Trisakti, 2023)
Due to the time, the steel truss had been used in several roof application. Several analysis structure methods codes had been developed and adopted for steel building constructions design and analysis. Recently, some finite element analysis also had completed the structure analysis. This research had modelled and analyzed the howie type of roof steel truss structure. The direct stiffness method had been compared to the finite element method (FEM) that was utilized by SAP2000. The stress analysis had been evaluated by performing 3D solid tension and compression member by utilizing Abaqus. The National Standard of Indonesia for steel construction (SNI 1729 2020) that was also verified by AISC/ANSI 360 2022 had been considered in this research. The results showed similarity between Direct Stiffness Method and FEM about 1% - 2%. The maximum tension stress on bottom chord had been verified by 3D solid respectively 175 MPa (ASD) and 213 MPa (LRFD) for yielding criteria. For fracture criteria the stress was recorded consecutively 140 MPa (ASD) and 260 MPa (LRFD). The compression member had been recorded correspondently 267 MPa (ASD) and 270 MPa (LRFD). The stress number that was occurred on the top chord had satisfied the design requirements accorded to AISC/ANSI 360-2022. However, in the case of compression member should be designed in double cross section for preventing the buckling failure.